Protocol for closed-loop optogenetic manipulation of cortical activity following hippocampal sharp-wave ripples in freely behaving rats - Hanna den Bakker; Jyh-Jang Sun; Marine Guyot; Fabian Kloosterman (STAR Protocols)
Summary: Temporally and spatially selective closed-loop perturbation of brain activity can be used to reveal the contribution of spontaneous neural events to behavior. Here, we present a protocol for optogenetic inhibition of the medial prefrontal cortex following hippocampal sharp-wave ripple events in freely behaving rats. We describe procedures for injecting a viral vector bilaterally, constructing and implanting an assembly of optical fibers and tetrodes, and performing closed-loop perturbations in rats.For complete details on the use and execution of this protocol, please refer to den Bakker et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.